Temperature dependent fracture toughness of KNN-based lead-free piezoelectric ceramics - Li, Yingwei; Liu, Yixuan; Öchsner, Paul-Erich; Isaia, Daniel; Zhang, Yichi; Wang, Ke; Webber, Kyle Grant; Li, Jing Feng; Rödel, Jürgen (Acta Materialia, 2019)
The fracture toughness of unpoled and electrically poled lead-free KNN-based piezoelectric ceramics with the composition of 0.92KNN-0.02Bi0.5Li0.5TiO3-0.06BaZrO3 was investigated. Results reveal that at room temperature, the intrinsic fracture toughness (KI0) of the unpoled samples, evaluated by the near-tip crack opening displacement (COD) technique, is the lowest with a value of 0.70 MPa⋅m0.5; the long (through-thickness) crack fracture toughness (KIvnb), obtained by the single edge V-notch beam (SEVNB) technique, is the highest, with a value of 0.95 MPa⋅m0.5; intermediate short surface crack fracture toughness (KIsc) of 0.86 MPa⋅m0.5 was determined by the surface crack in flexure (SCF) technique. These results were rationalized by the toughening behavior of the material combined with the crack geometry-dependent stress intensity evolution during crack propagation. With increasing temperature, KIvnb and KIsc decrease, and become nearly identical at 350 °C, suggesting an absence of toughening. For electrically poled samples, their room temperature fracture toughness was characterized by both SCF and SEVNB techniques, with values of 0.88 MPa⋅m0.5 and 0.99 MPa⋅m0.5, respectively, slightly larger than the values measured for unpoled samples. Nonlinear electric field-strain and stress-strain analysis of the material was also employed during electric field loading, mechanical compression and four-point bending in order to quantify crack tip shielding by domain switching and the actual stress at the point of instable crack propagation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Domain switching; Fracture toughness; Lead-free piezoceramics; Potassium-sodium niobate; Toughening